Distinctiveness of Japan - Ronald Dore (Journal of Economic Sociology, 2010)
The author follows the topic of variety of capitalism which became popular in 1990-2000 as antithesis to abstract discussions about globalization. The paper comprises the comparative analysis of Anglo-Saxon and Japan models of firm organization and its position on the market. Here the two approaches face each other: the first one defines firm as mostly the ownership structure and the second one treats firm as the universal society the activity of which depends on the managers’ and employees’ interests.